Toward a continuous improvement for justice - Sandoval, Carlos; Neri, Rebecca Colina (Frontiers in Education, 2024)
An emerging body of research on equity has begun to identify how equity can be fostered in continuous improvement (e.g., Valdez et al., 2020; Bush-Mecenas, 2022; Jabbar & Childs, 2022). However, our conceptual paper argues for the need for continuous improvement (CI) work to begin moving beyond equity and towards justice. To do so, we first offer conceptualizations of equity and justice in CI work, highlighting that equity concerns reducing disparities in dominant outcomes while justice focuses on improving towards outcomes that are concerned primarily with affirming, dignifying, and granting agency to Black, Brown, working-class, and other marginalized students. We draw on critical race theories and critical design research to illustrate the distinction between equity and justice, drawing parallels to design research as a body of knowledge that can inform the trajectory of CI as a field as it moves towards justice. Our paper offers examples of equity- and justice-focused continuous improvement projects and initiatives, recognizing the value and importance of equity work while simultaneously offering a critique of that work to uplift an orientation towards justice. We then generate a set of tenets for a justice-focused continuous improvement approach. We test and illustrate these principles using past and ongoing CI work. We offer directions for future practice and research that can advance the field towards justice and liberation in CI and beyond equity, articulating where we envision the capacity- and field-building work ought to take place in order to center justice in CI.